Analisis Makna Puisi “Penunggu Gunung Berapi” Karya W.S. Rendra: Kajian Semiotik Barthes: Penelitian - Kadir, Herson (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Poetry is a poet's interpretation of life, the use of diction rich in meaning in poetry is an important element that gives aesthetic value to literary works. One poem that describes a deep meaning and deserves to be explored in a complex way is